The philosophy of John Scottus Eriugena a study of idealism in the Middle Ages - Moran, Dermot 1953- (Cambridge University Press, 1989)
This work is a substantial contribution to the history of philosophy. Its subject, the ninth-century philosopher John Scottus Eriugena, developed a form of idealism that owed as much to the Greek Neoplatonic tradition as to the Latin fathers and anticipated the priority of the subject in its modern, most radical statement: German idealism. Moran has written the most comprehensive study yet of Eriugena's philosophy, tracing the sources of his thinking and analyzing his most important text, the Periphyseon. This volume will be of special interest to historians of mediaeval philosophy, history, and theology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Erigena, Johannes Scotus / approximately 810-approximately 877; Johannes -- Scotus Eriugena -- 810-877; Philosophy, Medieval; Idealism; Philosophie; Hochschulschrift